Local nearrings on finite non-abelian 2-generated p-groups - Raievska, I.Yu.; Raievska, M.Yu. (Carpathian Mathematical Publications, 2020)
It is proved that for p>2 every finite non-metacyclic 2-generated p-group of nilpotency class 2 with cyclic commutator subgroup is the additive group of a local nearring and in particular of a nearring with identity. It is also shown that the subgroup of all non-invertible elements of this nearring is of index p in its additive group.